Nurses and supervision of clinical training - Galvão, Ana Maria (2014)
Clinical supervision gains an important role, understood as a process of guidance, monitoring and support of students, that makes the learning process easier and promotes personal and professional skills. The objective of the study is to analyze the prespetiva nurses on the management of clinical education in undergraduate nursing, because they are the ones who daily deal with the problems of educational, organizational, functional, ethical and professional countenance in the supervision of Clinical Training students. Methods: It’s an explorative, descriptive, correlational and transversal study, with quantitative nature, that comes next to an inquiry of questions, using CICRS (Clinical Instructor Characteristics Ranking Scale). Results: From the results, we point out the fact that supervisor nurses are mainly female, with ages between 30 and 39 years, with college degree, and professional experience between 10 and 19 years. The most valued aspects are Nurse and Human Being. To the extent Teacher the most important indicator was on average transmit knowledge (6.55). For the Nurse dimension: to be competent as a nurse (9.92). To the Person dimension: be honest (9.19). Conclusions: This study presents various important aspects to set the management of the supervising process, assuring the responsibility of the participants and promoting the safety and the quality of performances in the Nurse Clinical Teaching.